ANALISIS EFISIENSI BANK UMUM SEBELUM DAN SETELAH KRISIS EKONOMI 2008 DENGAN MENGGUNAKAN METODE NON PARAMETRIK DATA ENVELOPMENT ANALYSIS (DEA) - Suharno, Arfinda Piradipta; Demi Pangestuti, Irene Rini (Faculty of Economics and Business Diponegoro University, 2014)
The economic crisis that occurred in quarter IV of 2008 until the quarter II 2009 which took place in the world including Indonesia handy, have resulted in a variety of global financial institutions suffered losses and bankruptcy. Bankruptcy that plagued banks-banks in Indonesia is affected by bank accepted deposits increased, while loans provided decreased, leading to increased interest on loans given to banks.Population research used are commercial banks listed on the IDX (Indonesia stock exchange) period 2006-2012. This study used the method of DEA (Data Envelopment Analysis) and test different ANOVA.The results of hypothesis testing with different ANOVA test showed the presence of tidal differences in the efficiency of banking performance before and after the economic crisis. The results can provide advice to companies banking on anticipated at the time of the crisis, bank indonesia concerning the banking performance evaluation andimplementation of the industrial policy of banks, borrowers, investors, banks and stockholders about the banking efficiency information at the time of the crisis.